PENGEMBANGAN MEDIA PEMBELAJARAN GAME BASED LEARNING BERBASIS KURIKULUM MERDEKA BELAJAR UNTUK PEMBELAJARAN BAHASA ARAB DI MI SALAFIYAH SYAFI'IYAH AR-RAHMAH NGLABAN JOMBANG - Fatkhur Rizal, Muhammad; Rahmawati, Chusnia; Kristianto, Hery; Lazulfa, Indana; Rizqi Salamah, Evi; Kistofer, Terdy (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
In the Independent Curriculum (Kurikum Merdeka), educators or teachers are given latitude in selecting and compiling teaching materials according to student’s needs and characteristics. The flexibility given to teachers in teaching and learning activities aims to make teachers more creative in developing appropriate teaching methods and materials. Likewise, when learning Arabic, educators can select relevant teaching materials but still refer to the learning outcomes that have been formulated. This certainly makes it easier for teachers to develop teaching materials based on student competencies and profiles. One of the easiest learning media to apply is an Android-based application. This dedication is to develop teaching materials based on learning by adding features that suit the needs and interests of users of this application, which can help improve Arabic language learning. The results of learning using games based on learning obtained an average assessment score on a Likert scale (1-5) with a score of 4.83 in terms of ease of User Interface, and 4.82 in terms of content suitability of the material. Then as many as 82.93% of respondents stated that they strongly agreed with the ease of the User Interface, and 81.71% of respondents stated that they strongly agreed with the material suitability content.